2004
DOI: 10.1182/blood-2003-09-3311
|View full text |Cite
|
Sign up to set email alerts
|

Do thymically and strictly extrathymically developing T cells generate similar immune responses?

Abstract: IntroductionOne hallmark of the adaptive immune system is that the thymus has been conserved as the primary T-lymphoid organ during 450 million years of evolution. 1 This level of conservation is remarkable when one considers that about 10 different organs have been used as primary sites of hematopoiesis in jawed vertebrates. 1 Thymic epithelial cells (TECs) derived from the third pharyngeal pouch are the main constituent of the thymic environment. 2 TECs provide 2 types of signals to thymocytes: T-cell recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…50 Extrathymic de novo generation of donor T cells observed in our studies may also provide some protection from MCMV infection, 50 despite their lower number and poorer function compared with thymic-derived T cells. 11,51 In summary, our findings offer new insights into the contribution of Tregs in maintaining an optimal microenvironment for the reconstitution of functional immunity. Protection of the thymic and nodal niches in which T-cell generation and homeostasis occur is a major mechanism by which Tregs mediate their protective effects, and may help explain the intrinsic link between the suppression of GvHD and an enhancement of immune reconstitution following adoptive transfer of Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…50 Extrathymic de novo generation of donor T cells observed in our studies may also provide some protection from MCMV infection, 50 despite their lower number and poorer function compared with thymic-derived T cells. 11,51 In summary, our findings offer new insights into the contribution of Tregs in maintaining an optimal microenvironment for the reconstitution of functional immunity. Protection of the thymic and nodal niches in which T-cell generation and homeostasis occur is a major mechanism by which Tregs mediate their protective effects, and may help explain the intrinsic link between the suppression of GvHD and an enhancement of immune reconstitution following adoptive transfer of Tregs.…”
Section: Discussionmentioning
confidence: 99%
“…These AndoNude cells might have appeared by an immunoselection of rare HLA-negative cells, in which extrathymic T lymphocytes present in nude mice might have been implicated, 20,21 although it has been shown that these extrathymic T lymphocytes cannot functionally substitute classic thymic T cells. 22 It is also possible that NK cells present in nude mice might xenogenically recognise Ando-2 melanoma cells and produce immunoselection of AndoNude melanoma cells. However, SCID-Beige mice have neither T lymphocytes nor NK cells, and Ando-2 melanoma cells presented a strong HLA class I down-regulation after their passage in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in oncostatin M-transgenic mice infected with lymphocytic choriomeningitis virus have allowed us to evaluate the protective value of innate T cells in the absence of conventional T cells (66). In this model, innate CD8 T cells could not substitute for conventional T cells in providing long-term control of infection, because they underwent proliferative exhaustion and apoptosis (10,67). Nevertheless, innate CD8 T cells initiated proliferation swiftly, secreted copious amounts of IFN-g, and were able to provide initial control of lymphocytic choriomeningitis virus infection.…”
Section: Discussionmentioning
confidence: 99%